Physiological and biochemical responses in Calotropis procera callus under salt stress and signalling inducers - Alam, Maqsood (2024)
The latex of Calotropis procera has been previously documented to contain pathogenesis-related (PR) proteins, specifically osmotin, chitinase, and protease known for their defensive functions in the plant. This study examined the temporal expression profiles of CpOsm, CpChit, and CpProt transcripts in C. procera callus under salt stress and signalling inducers, Salicylic acid (SA) and Methyl jasmonate (MeJA), aiming to elucidate their roles in physiological aspects in connection with plant defence mechanisms. Under salt stress, calli showed reduced water content, growth, and fresh weight (FW), with the strongest effects observed at 100 mM NaCl. Catalase (CAT) and ascorbate peroxidase (APX) activities were decreased at 80 mM NaCl, while peroxidase (POX) was lowest in control and 60 mM NaCl, and superoxide dismutase (SOD) decreased at 100 mM NaCl. Proteolytic activity and soluble proteins increased at 80 mM NaCl, and hydrogen peroxide activity peaked at 100 mM NaCl. In particular, the levels of chlorophyll a, b, and carotenoid were increased at 80 mM NaCl. Confocal microscopy revealed reduced chlorophyll in 100 mM NaCl, low phenols in 80 mM NaCl, and high lignin in 100 mM NaCl. DNA integrity was preserved, indicating stimulated cellular proliferation under salt stress. SDS-PAGE and Zymogram showed increased protein levels at 100 mM NaCl. Transcriptional analysis revealed an upregulation of CpOsm, CpChit, and CpProt in response to salt stress, which peaked at different time points, indicating their involvement in stress adaptation. The SA treatments 200 and 400 μM reduced the water content in the callus, in contrast to the MeJA treatments, which increased the water content. SA 400 μM inhibited growth, with 100 μM leading to low dry weight (DW). The MeJA treatments did not affect growth, but all treatments reduced DW. SA 400 μM decreased CAT and APX, while MeJA 50 μM increased them. POX and SOD levels increased in both 400 μM SA and 50 μM MeJA-treated callus compared to the control. The proteolytic activity and the soluble proteins decreased with SA 400 μM, while MeJA 50 μM showed remarkably low values. The chlorophyll content increased in the SA treatments compared to the calli treated with MeJA. SDS-PAGE and zymogram evaluations showed increased protein concentrations in the presence of 400 μM SA and 200 μM MeJA. Transcriptional analysis revealed the upregulation of CpOsm, CpChit, and CpProt, providing insights into the responsiveness of these genes under SA and MeJA treatments. The study enhances comprehension of the intricate interaction between salinity and signalling molecules in C. procera callus culture. Osmotin, chitinase, and protease genes are highly responsive, indicating their role in combating both biotic and abiotic stress. Furthermore, their expression is enhanced during signalling molecule-mediated responses.